1989
DOI: 10.1007/bf00140132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects and prevention of Q fever in animals

Abstract: The natural reservoir of Coxiella burnetii encompasses many free-living vertebrates but the major risk of human infection arises through contact with infected ruminant livestock and their contaminated products. The organism has a remarkable affinity for the ruminant placenta and mammary gland but the great majority of naturally-occurring infections are asymptomatic. However, the potential of C. burnetii to cause abortion has been demonstrated experimentally and observed in the field while more recent evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 20 publications
1
52
0
1
Order By: Relevance
“…8 The results reported here suggest that Coxiella are not commonly found in the placentas of aborting dairy cattle yet researchers have shown that the organism can be easily cultured from the placenta, reproductive fluids, and milk of cattle at the time of parturition. 1,11 The culture technique is undoubtedly a more sensitive detection method than those employed here but it is also possible that alterations in the immune system and the hormonal environment at the time of parturition favor the growth of Coxiella. Rickettsial proliferation at this time may occur too rapidly to permit an inflammatory response from the fetus before parturition is completed, explaining the lack of placental lesions reported by some authors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…8 The results reported here suggest that Coxiella are not commonly found in the placentas of aborting dairy cattle yet researchers have shown that the organism can be easily cultured from the placenta, reproductive fluids, and milk of cattle at the time of parturition. 1,11 The culture technique is undoubtedly a more sensitive detection method than those employed here but it is also possible that alterations in the immune system and the hormonal environment at the time of parturition favor the growth of Coxiella. Rickettsial proliferation at this time may occur too rapidly to permit an inflammatory response from the fetus before parturition is completed, explaining the lack of placental lesions reported by some authors.…”
Section: Discussionmentioning
confidence: 97%
“…1 Serologic evidence of a high rate of Coxiella infection in cattle has resulted in considerable concern regarding the zoonotic potential of bovine coxiellosis. 2,8 However, the pathogenic consequences of this rickettsial infection to the bovine host have received relatively little attention, especially in North America.…”
mentioning
confidence: 99%
“…The main route of C. burnetii infection is by inhalation of contaminated aerosols containing the microorganism shed from infected animals [1,25,26,28,30,31,34,35]. After becoming infected, female animals shed large quantities of Coxiella into the 424 N. Arricau Bouvery et al environment during abortion or normal delivery through birth fluids, placenta and fetal membranes [3,6,23,24,32]. Moreover, following parturition, these infected animals excrete the bacteria via the urine, feces, vaginal discharges and milk for several months [10,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Infected animals, like goats, sheep, and cattle, often show no clinical signs of infection except for abortions or stillbirths that may occur due to the infection of the placenta (2,21,25).…”
mentioning
confidence: 99%